Wisdom to attain happiness in Vedic culture perspective - Yulianti, Ni Ketut Dewi; Ardini, Ni Wayan; Darmayuda, I Komang (Linguistics and Culture Review, 2023)
This paper discusses about wisdom to attain happiness. Happiness is experienced when the soul attained peace, while peace can be attained when people have wisdom. Wisdom is often understood by different perspectives. Therefore, in this paper, it is explained from the perspective of the Vedic culture perspective, namely of the scripture Srimad-Bhagavatam (Vedanta Sutra), which is the highest source of knowledge. This paper can be used as a reference especially for students and teachers who want to go deeper into character education, since self-realization – which is the foundation of character education – is also a part of wisdom. There are two topics discussed in this paper, namely (a) wisdom influenced by the three modes of material nature and (b) the real wisdom to attain real happiness. The real wisdom referred to here is the wisdom that begins from self-realization. Theoretically, this paper will be able to contribute to the world of education especially in the field of character education, so that it can contribute to the successfulness of the national education.